Pengembangan M-Kamus Istilah Penelitian dalam Bahasa Arab bagi Mahasiswa Pendidikan Bahasa Arab Universitas Negeri Semarang - Muhammad Hakim Azzikri (LISANIA: Journal of Arabic Education and Literature, 2019)
The purpose of this research was to develope a special dictionary based on Android mobile applications or m-Dictionary of Research Terms in Arabic. The type of this research was research and development (R D). The data were obtained through non-tests, namely questionnaires for student needs, questionnaires for expert validation tests, and interviews. The conclusion that can be taken from this study is that the students need a special dictionary based on Android mobile applications or M-Dictionary of Research Terms in Arabic which contains research terms in Arabic with the main components in the mdictionary based on needs analysis are the main page, search, bookmark, usage instructions, profile, about M-Dictionary, and suggestions. Based on the results of the application validation test questionnaire, M-Dictionary of Research Terms in Arabic gets a total value of 86.57 which means that application of the m-Dictionary of Research Terms in Arabic is feasible to use